Andy Kaufman : Wrestling with the American Dream - Keller, Florian (Book collections on Project MUSE., 2005)
Taking as his starting point the 1999 biopic Man on the Moon, Florian Keller explores Andy Kaufman's career within a broader discussion of the ideology of the American Dream, grasping Kaufman's radical agenda beyond avant-garde theories of transgression. Presenting readings of Kaufman's most significant performances, Keller shows how he mounted a critique of America's obsession with celebrity and individualism.